THE INFLUENCE OF SHOPEE'S E-COMMERCE FEATURES ON ISLAMIC CONSUMPTION BEHAVIOR: A CASE STUDY OF STEI STUDENT AR-RISALAH CIAMIS - Garnita Ulfah Fauziah; Nila Nurochani (Syari'ah Economics, 2022)
This study aims to determine: The effect of Shopee's E-Commerce Facilities (Features) on student consumptive behavior. The data collection techniques uses a questionnaire method with a population of STEI Ar-Risalah students for the 2018-2021 academic year who have the Shopee Application, where purposive sampling is used as a sampling technique. IBM statistical application version 26 is used to assist researchers in analyzing research data through simple linear regression analysis. The results of this study show that the Shopee E-Commerce feature has an effect on student consumptive behavior. This is indicated by the results of the t test which shows the tcount value is greater than ttable (19.295 > 1.667) and a significance value of 0.000 which means it is smaller than the standard 0.05.